Pengembangan Lembar Kerja Siswa Pelajaran Bahasa Indonesia Berbasis Cerita Anak Sekolah Dasar - Ahmad Sarjuni; Muhammad Fuad; Nurlaksana Eko Rusminto (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2017)
The development model used in this research is Borg and Gall's research and development (R D), which is furthermore known as research and development research (RDR) with the steps adapted by researchers. The research and development research (RDR) model is grouped into three activities, namely preliminary research, product development, and effectiveness test. The results of a small classroom test using the instrument shaped the student worksheet. The number of questions is 20 in the form of multiple choice. The results of the test in the large class, indicating that of the 20 questions given in the form of multiple choice questions obtained an average value of 87.3. Based on these results, the learning materials based on the story of LKS get very good predicate to be used as teaching materials. Based on the questionnaire of the feasibility test of the teaching materials in the big class in the three schools obtained the average data score of 3.9 the teaching materials are very feasible to use.Model pengembangan yang digunakan dalam penelitian ini adalah research and development (RD) Borg and Gall yang selanjutnya lebih dikenal dengan research and development research (RDR) dengan langkah-langkah diadaptasi oleh peneliti. Model research and development research (RDR) dikelompokkan menjadi tiga kegiatan, yakni penelitian pendahuluan, pengembangan produk, dan uji efektivitas. Hasil uji coba pada kelas kecil menggunakan instrumen berbentuk soal lembar kerja siswa. Jumlah soal berjumlah 20 berbentuk pilihan ganda. Hasil uji pada kelas besar, menunjukkan bahwa dari 20 pertanyaan yang diberikan dalam bentuk soal pilihan ganda diperoleh nilai rata-rata 87,3. Berdasarkan hasil tersebut maka bahan ajar LKS berbasis cerita memperoleh predikat sangat baik untuk dipergunakan sebagai bahan ajar. Berdasarkan angket uji kelayakan bahan ajar pada kelas besar di tiga sekolah diperoleh data rata-rata skor 3,9 bahan ajar sangat layak untuk digunakan.Kata kunci: Pengembangan,bahan ajar.